(untitled) (Bangladesh Pharmaceutical Journal, 2026)
This study aimed to evaluate the quality attributes of marketed 10 mg domperidone tablets available in Bangladesh, providing a comprehensive assessment of their pharmaceutical performance in line with British Pharmacopoeia (BP) standards. The study examined granule flow properties, including angle of repose, bulk density, tapped density, compressibility index as well as critical tablet characteristics such as weight variation, hardness, friability, thickness, diameter, disintegration, potency and dissolution behavior. Four branded tablets of renowned pharmaceuticals of Bangladesh and formulated tablets demonstrated compliance with BP specifications for weight, diameter and thickness indicating uniformity in size and consistent mass distribution. Mechanical strength and disintegration assessments revealed that all samples possessed sufficient hardness and moderate disintegration profiles, although some marketed tablets occasionally exhibited slightly lower hardness compared to formulated counterparts. Dissolution testing confirmed that all tablets released ≥75% of their active ingredient within 45 minutes, meeting BP requirements for immediate-release dosage forms. Potency analysis further indicated that the active pharmaceutical ingredient content ranged between 90% and 110% across all products, reflecting accurate dosing and reliable therapeutic potential. These results collectively affirm that both marketed and formulated 10 mg domperidone tablets fulfill pharmacopeial standards, supporting their safety, efficacy and suitability for patient use. Bangladesh Pharmaceutical Journal 29(1): 107-118, 2026 (January)